Hypomagnesemia is associated with increase in mortality and morbidity in ICU: Can serum magnesium level be used as prognostic marker in critically ill ICU admitted patients? - Islam, Md Motiul; Faruq, Mohammad Omar; Asaduzzaman, Mohammad; Sultana, Amina; Mollick, Uzzawl Kumar (Bangladesh Critical Care Journal, 2017)
Objective: Hypomagnesemia is one of the common electrolyte disorders found in critically ill patients. It is often an incidental finding and usually its importance is ignored. This study was designed to assess the significance of the impact of hypomagnesemia on the mortality and morbidity of the ICU patients. Hence the efficacy of hypomagnesemia as prognostic marker was also tested. Method: Prospective cohort study done at the department of Critical Care Medicine, of a tertiary care hospital in the city of Dhaka, Bangladesh (from January 2014 to December 2014) aiming to find out of the differences in mortality & morbidity between two groups of patients one with low and other with normal Mg level. Result: 95 adult ICU admitted patients were included in the study and 38% of the study subjects were found to be Hypomagnesemic. The Hypomagnesemic group of patients needed more frequent ventilator support (75% vs 52.54%, p<0.02) and the duration of mechanical ventilator support was also prolonged (3.88±4.10 vs 2.25±3.18, p<0.04, in days). Hypomagnesemic group also needed prolonged ICU stay (9.13 vs 6.27, p<0.01) and total hospital stay (14.94 vs 10.47, p<0.007, days). Hypomagnesemic group of patients had more abnormal total leukocyte count (69.4% vs 47.5%, p <0.05) and more frequent use of inotropic support (61.1% vs 38.9%, p <0.05). The 28 days mortality rate in Hypomagnesemic patients were also high (33.3% vs 11.86%, p<0.01). Conclusion: In this study it was observed that Hypomagnesemia was significantly associated with adverse outcome. So it is better not to ignore this important confounder to predict the outcome of the critically ill ICU admitted patient. Considering the increasing demand of more accurate prognostic marker in critically ill patient, it maybe the high time to utilize serum Mg level systematically for outcome prediction. Bangladesh Crit Care J September 2017; 5(2): 77-82